Studies of culverts on the high-speed section of the Tashkent-Sirdarya Railway Line - Abdualiyev Elyorbek Begaliyevich; Maxamadjonov Shuxrat Shavkatovich; Uralov Akmal Shakarovich (Research Parks Publishers, 2021)
This article shows the study of culverts, which are the most common type of artificial structures in roads and railways. For the passage of water at the intersections of watercourses with the roadbed, culverts are arranged, which, depending on the topographic, hydrological, geological and other conditions, can be of various types